2011
DOI: 10.1002/j.0022-0337.2011.75.6.tb05103.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness Course in the Dental Curriculum and Prevention of Low Back Pain

Abstract: Physical and psychosocial stressors in dental schools are associated with adverse health outcome, including low back pain. The aim of this study was to evaluate the physical itness course included in a dental school's curriculum with regard to prevention of low back pain. Ninety irst-year and sixty-two inal-year dental students completed an anonymous questionnaire on physical itness habits and low back pain. Fifty voluntarily participated in the Åstrand bicycle ergometer test. The questionnaire revealed that 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 22 publications
1
26
1
2
Order By: Relevance
“…However, when analyzed, the lower body was found to be affected to a lesser extent, and the majority of the discomfort or pain in these areas is due to the fact that students do not work with their feet supported on the floor 11 . A good sitting position, with a support base of the expanded body, avoids potential changes in the circulatory system, such as varicose veins, edema, pain, and inflammation, which may occur as a result of muscle compression of the lower extremities which impedes venous return 7 .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…However, when analyzed, the lower body was found to be affected to a lesser extent, and the majority of the discomfort or pain in these areas is due to the fact that students do not work with their feet supported on the floor 11 . A good sitting position, with a support base of the expanded body, avoids potential changes in the circulatory system, such as varicose veins, edema, pain, and inflammation, which may occur as a result of muscle compression of the lower extremities which impedes venous return 7 .…”
Section: Discussionmentioning
confidence: 97%
“…In this study, a high prevalence of painful symptomatology was observed in the study population; indeed, high pain rates have been previously reported by dentists of both sexes, with early onset 5 . These indexes were also high when only the students who already perform activities clinical practices were analyzed 11,12 . In a study using the RULA methodology, we found a high risk for the development of musculoskeletal disorders and, especially, in the upper limbs, of the students who were performing preclinical activity 11 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Mechanisms leading to work-related musculoskeletal disorders are multi-factorial. Factors impacting on the risk of injury from biomechanical hazards are mainly physical like exertion, prolonged static postures, movement and repetition, suboptimal lighting, poor positioning and bad body posture, exposure and vibration, genetic predisposition, but could also have psychosocial origin, mental stress, physical conditioning, age and obesity [14,16,35]. aging is considered as a strong risk factor for musculoskeletal disorders.…”
Section: Biomechanical Hazardsmentioning
confidence: 99%